Challenging The Investigator’s Investigation Termination Authority Without Public Prosecutor’s Approval - Jefferson Hakim (Universitas Brawijaya, 2024)
The principle of dominus litis is owned by the Public Prosecutor as the master of the case in the criminal justice system. The Public Prosecutor has a central role in criminal law enforcement which begins when following the progress of the investigation carried out by investigators to the execution of court decisions that obtain permanent legal force. However, the Criminal Procedure Law seems to exclude the absolute authority of the Public Prosecutor as the master of the case concerning the investigator’s authority to terminate an investigation without prior approval of the Public Prosecutor. This resulted in the Public Prosecutor not having a control function over the investigation executed by investigators with the potential for abuse of authority. The research method used in this study is normative juridical with descriptive analysis. This study used secondary and tertiary data, which were prepared and analysed according to the discussion in this study. The study reveals that the investigator’s authority to stop the investigation without prior approval from the Public Prosecutor is contrary to the principle of dominus litis attached to the Public Prosecutor associated with the Guidelines on the Role of the Prosecutor and the authority of the Public Prosecutor in England and Wales and South Korea.